PENGARUH JUMLAH CACING TANAH (LUMBRICUS RUBELLUS) DAN WAKTU PENGOMPOSAN TERHADAP C/N RASIO VERMIKOMPOSTING DARI SLUDGE IPAL PT SURABAYA INDUSTRIAL ESTATE RUNGKUT (SIER) - Naniek Ratni J.A.R; Faisal Aziz Faisal (EnviroUS, 2021)
Along with the development of a country, industrial growth in that country will increase. As industrial development increases, the waste generated will also continue to increase. PT SIER's waste treatment process produces by-products in the form of sludge from the Aktif sludge treatment process, one of which is the composting process using the vermicomposting method with the help of earthworms (Lumbricus rubellus). This study aims to determine the effect of the number of earthworms (Lumbricus rubellus) on the C/N ratio of vermicomposting from WWTP sludge at PT. Surabaya Industrial Estate Rungkut (SIER) and to determine the effect of composting time on C/N ratio of vermicomposting from sludge WWTP PT. Surabaya Industrial Estate Rungkut (SIER). This study used a reactor size of 20 cm high, the type of earthworm (Lumbricus rubellus) with a length of 7-10 cm, 1.5 kg of sawdust and 5 kg of sludge with a sampling time of 7 days, 14 days, 21 days, 28 days, and 32 days. day. The results of this study showed that composting using earthworms (Lumbricus rubellus) could reduce the content of the C/N ratio by 14.89 in reactor 5 with the number of worms 30 on the 32nd day of composting and the lowest decrease was 23.51 in reactor 1 with the number of worms. 10 worms with a composting time of 32 days